Analisis preferensi konsumen terhadap daging ayam kampung dan ayam broiler di pasar tradisional Kota Kupang - Melliany Anggelina Ottu (Fakultas Pertanian Universitas Majalengka, 2025)
This study aims to analyze consumer preferences for free-range and broiler chicken in traditional markets in Kupang City. Data were collected from 50 respondents selected through accidental sampling at three purposively chosen traditional markets—Oebobo, Oeba, and Inpres Naikoten—between 5 and 25 October 2025. Primary data were obtained through interviews and questionnaires, while secondary data were sourced from institutional reports and relevant literature. Descriptive statistics were used to identify consumer characteristics and attribute evaluations, followed by an independent samples t-test or Mann–Whitney U test to assess differences in preferences between the two types of chicken. The results show that consumers exhibit a stronger preference for free-range chicken due to its richer flavor profile, firmer texture, and greater perceived health value, positioning it as a premium-quality product. In contrast, broiler chicken is primarily chosen for its affordability, high market availability, and practicality in food preparation, making it the most feasible option for daily household consumption. The Mann–Whitney U test returned a significance value of < 0.05 for all assessed attributes, confirming statistically significant differences in consumer preferences between the two chicken types. Overall, these findings indicate distinct market segmentation, where free-range chicken appeals to consumers who prioritize sensory quality and health attributes, while broiler chicken dominates routine demand driven by economic and efficiency considerations. The results are expected to serve as a strategic reference for market actors and policymakers in developing poultry marketing strategies and food policy interventions